Application of Transformational Leadership Method to Increase Job Satisfaction - Jemmi Halil Amiruddin; Ananta Yudiarso (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
This study used meta-analysis through a literature review of 20 international research journals involving 5,047 participants from various professional backgrounds according to the research. This study aims to look at the relationship between leadership style (transformational leadership) and job satisfaction. The method used is meta-analysis with jamovi 1.2.27.0 using the Multifactor Leadership Questionnaire, Minnesota Satisfaction Questionnaire, Path-Goal Theory of Leadership Questionnaire and Job Satisfaction Survey/Scale measurement tools. The results obtained are that Transformational Leadership is effective in increasing job satisfaction (d=0.68; large effect size). The results of this study indicate that the transformational leadership style has a significant effect on increasing job satisfaction. The style of transformational leadership has a significant effect on job satisfaction in a good work environment, a good salary system, and certainty of the status of employees. It will be different if this leadership style is applied to organizations that still need a good work environment, a salary system that is not yet good, and the status of employee is uncertain.Penelitian ini menggunakan meta-analisis melalui review literatur 20 jurnal penelitian internasional melibatkan 5.047 partisipan dari berbagai latar belakang profesi sesuai penelitian. Penelitian ini bertujuan untuk melihat hubungan antara leadership style dan job satisfaction. Metode yang digunakan adalah meta-analisis dengan jamovi 1.2.27.0 menggunakan alat ukur Multifactor Leadership Questionnaire, Minnesota Satisfaction Questionnaire, Path-Goal Theory of Leadership Questionnaire dan Job Satisfaction Survey/Scale. Hasil yang didapatkan ialah Transformational Leadership efektif dalam meningkatkan job satisfaction (d=0,68; large effect size). Dari penelitian ini dapat disimpulkan bahwa gaya kepemimpinan transformasional (transformational leadership) berpengaruh signifikan untuk meningkatkan kepuasan kerja (job satisfaction). Gaya kepemimpinan transformasional (transformational leadership) berpengaruh signifikan terhadap kepuasan kerja (job satisfaction) pada lingkungan kerja yang bagus, sistem penggajian yang bagus, dan kepastian status pegawai/karyawan. Akan berbeda apabila gaya kepemimpinan tersebut diterapkan pada organisasi yang masih membutuhkan lingkungan kerja yang bagus, sistem penggajian yang belum bagus, dan status karyawan/pegawai yang belum pasti.